2020
DOI: 10.1021/acschemneuro.0c00309
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Characterization of Cell Membrane Disruption by α-Synuclein Oligomers in Live SH-SY5Y Neuroblastoma Cells

Abstract: Aggregation of the natively unfolded protein αsynuclein (α-Syn) has been widely correlated to the neuronal death associated with Parkinson's disease. Mutations and protein overaccumulation can promote the aggregation of α-Syn into oligomers and fibrils. Recent work has suggested that α-Syn oligomers can permeabilize the neuronal membrane, promoting calcium influx and cell death. However, the mechanism of this permeabilization is still uncertain and has yet to be characterized in live cells. This work uses scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Kim et al [22] also found that α-Syn oligomers formed well-defined conductance states in a variety of membranes and that the beta-structure of these membrane-bound oligomers differed from that of α-Syn fibrils. Parres-Gold et al [24] used scanning ion conductance microscopy (SICM) to show that α-Syn oligomers induce morphological changes and formation of large transient pores in live SH-SY5Y neuroblastoma cells. Toxic α-Syn accumulation in SH-SY5Y is alleviated by membrane depolarization [62], suggesting that membrane interactions of α-Syn are related to toxicity in these cells.…”
Section: Equilibrium Among Type 2 Oligomers Protofibrils and Fibrilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [22] also found that α-Syn oligomers formed well-defined conductance states in a variety of membranes and that the beta-structure of these membrane-bound oligomers differed from that of α-Syn fibrils. Parres-Gold et al [24] used scanning ion conductance microscopy (SICM) to show that α-Syn oligomers induce morphological changes and formation of large transient pores in live SH-SY5Y neuroblastoma cells. Toxic α-Syn accumulation in SH-SY5Y is alleviated by membrane depolarization [62], suggesting that membrane interactions of α-Syn are related to toxicity in these cells.…”
Section: Equilibrium Among Type 2 Oligomers Protofibrils and Fibrilsmentioning
confidence: 99%
“…Eichmann et al [19] have published EM images of high-density lipoproteins formed by all three families of synucleins in the presence of sphingomyelin. Also, numerous studies have found that α-Syn permeabilizes membranes and forms channels in both artificial membranes [2023], and neural cells [2426].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [22] also found that α-Syn oligomers formed well-defined conductance states in a variety of membranes and that the beta-structure of these membranebound oligomers differed from that of α-Syn fibrils. Parres-Gold et al [24] used scanning ion conductance microscopy (SICM) to show that α-Syn oligomers induce morphological changes and formation of large transient pores in live SH-SY5Y neuroblastoma cells. Toxic α-Syn accumulation in SH-SY5Y is alleviated by membrane depolarization [62], suggesting that membrane interactions of α-Syn are related to toxicity in these cells.…”
Section: ηιγη δενσιτψ λιποπροτεινς: γ-σψνmentioning
confidence: 99%
“…Eichmann et al [19] have published EM images of high-density lipoproteins formed by all three families of synucleins in the presence of sphingomyelin. Also, numerous studies have found that α-Syn permeabilizes membranes and forms channels in both artificial membranes [20][21][22][23], and neural cells [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Also, numerous studies have found that α-Syn permeabilizes membranes and forms channels in both artificial membranes [20][21][22][23] and neural cells. [24][25][26] Several familial mutations that contribute to PD have been identified, most of which are sequentially near each other. However, it is unclear how or whether these alter oligomer conformations or the binding of this segment into a cleft within the Cyclophilin A protein.…”
mentioning
confidence: 99%